2012
DOI: 10.3109/14767058.2012.668582
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dilation as a predictor of pregnancy outcome following emergency cerclage

Abstract: Women who receive a rescue cerclage are more likely to deliver at an earlier gestational age when cervical dilation is ≥ 2 cm at the time of procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…With respect to other outcomes such as frequency of term delivery, Apgar score at 5 minutes, and birth weight, the efficacy of emergency cerclage was equivalent to that of elective cerclage. The frequency of cesarean delivery was lower in the emergency group (27%) than in the elective group (48%), which suggests that emergency cerclage does not influence the mode of delivery, consistent with recent reports . Some retrospective studies have reported higher rates of procedure‐related complications, but no surgical complications occurred in the present study population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to other outcomes such as frequency of term delivery, Apgar score at 5 minutes, and birth weight, the efficacy of emergency cerclage was equivalent to that of elective cerclage. The frequency of cesarean delivery was lower in the emergency group (27%) than in the elective group (48%), which suggests that emergency cerclage does not influence the mode of delivery, consistent with recent reports . Some retrospective studies have reported higher rates of procedure‐related complications, but no surgical complications occurred in the present study population.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have showed that membrane prolapse beyond the external os and/or a cervical dilation of 1.5 cm are independent predictors of cerclage failure. 8,10,13 In the present study, seven patients had cervical dilation at the time of the cerclage procedure, and most of these women had poor out- proposed cerclage for women with CL less than 15 mm, whereas a meta-analysis 15 has suggested that cerclage should be done for women with a previous history of preterm birth and CL less than 25 mm.…”
Section: Discussionmentioning
confidence: 59%
“…Although most studies report the use of some kind of prophylactic antibiotics, some do not [4,9,14,15]. Results in the latter studies do not seem to differ from those including the systematic use of antibiotics.…”
Section: Discussionmentioning
confidence: 64%
“…In fact, in the review by Namouz et al [1], only 5 studies [4,9,15,18,29] reported a higher number of cases, and another 3 [7,23,30] reported 40 cases or more. In addition, in most studies a standard protocol of management was not followed, and in some reports (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation